Subsurface 3D Prediction Porosity Model from Converted Seismic and Well Data Using Model Based Inversion Technique - Al-Rahim , Ali M.; Ali Hashem, Hassan (Iraqi Journal of Science, 2023)
Seismic inversion technique is applied to 3D seismic data to predict porosity property for carbonate Yamama Formation (Early Cretaceous) in an area located in southern Iraq. A workflow is designed to guide the manual procedure of inversion process. The inversion use a Model Based Inversion technique to convert 3D seismic data into 3D acoustic impedance depending on low frequency model and well data is the first step in the inversion with statistical control for each inversion stage. Then, training the 3D acoustic impedance volume, seismic data and porosity wells data with multi attribute transforms to find the best statistical attribute that is suitable to invert the point direct measurement of porosity from well to 3D porosity distributed volume. The final subsurface porosity model greatly improves the understanding of the distribution of porosity in the reservoir zones and showing the variations of porosity both vertically and laterally. The success of the prepared workflow encourage the transformation it automatically to run the same workflow faster for the areas that have the same characteristics of carbonate Yamama Formation.